Charakteristika und Beurteilungsansätze problemorientierter integrativer Umweltforschung - Schiller, Johannes; Manstetten, Reiner; Klauer, Bernd; Steuer, Philipp; Unnerstall, Herwig; Wittmer, Heidi (UFZ-Diskussionspapiere, 2005)
We analyze a dynamic and stochastic ecological-economic model of grazing management in semi-arid rangelands. The non-equilibrium ecosystem is driven by stochastic precipitation. A risk averse farmer chooses a grazing management strategy under uncertainty such as to maximize expected utility from farming income. Grazing management strategies are rules about which share of the rangeland is given rest depending on the actual rainfall in that year. In a first step we determine the farmer's short-term optimal grazing management strategy. We show that a risk averse farmer chooses a strategy such as to obtain insurance from the ecosystem: the optimal strategy reduces income variability, but yields less mean income than possible. In a second step we analyze the long-run ecological and economic impact of different strategies. We conclude that the more risk averse a farmer is, the more conservative and sustainable is his short-term optimal grazing management strategy, even if he has no specific preference for the distant future.
Parallel als Druckausg. erschienen
Keywords: Arbeitspapier; Graue Literatur